Pelatihan Pengembangan Website Pembelajaran Berbasis Weebly Untuk Guru Sagusaku IGI - Delina, Mutia; Iswanto, Bambang Heru (Mitra Teras: Jurnal Terapan Pengabdian Masyarakat, 2022)
Abstract One of the ways to prevent transmission of the Corona Virus (COVID-19) is to optimize the use of ICT by developing a website on physics learning for SMA in ISAGU IGI. Methods in website development activities will be carried out in two sessions, and the first session is to introduce Weebly and how to create a website using Weebly. The second session is to evaluate the website that has been made. The output of this activity is that each participant can create a website using Weebly for physics learning. The results of the PPM activities are videos on YouTube, and the learning module gets IPR. It can conclude that this learning website training is helpful during Distance Learning (PJJ) activities to help students understand the subject matter. Abstrak Salah satu cara mencegah penularan Virus Corona (COVID-19), yaitu melakukan optimalisasi pemanfaatan ICT dengan mengembangkan website dalam pembelajaran fisika untuk SMA di ISAGU IGI. Metode dalam kegiatan pengembangan website akan dilaksanakan dalam dua sesi, sesi pertama adalah memperkenalkan weebly dan cara membuat website dengan menggunakan weebly, dan sesi kedua adalah mengevaluasi website yang telah dibuat. Luaran dari kegiatan ini adalah setiap peserta mampu membuat website dengan menggunakan weebly untuk pembelajaran fisika. Hasil kegiatan PPM di videokan ke youtube, dan modul pembelajaran mendapatkan HAKI. Dapat disimpulkan bahwa, pelatihan website pembelajaran ini sangat berguna selama kegiatan Pembelajaran Jarak Jauh (PJJ) untuk membantu siswa memahami materi pelajaran.